PENATALAKSANAAN FISIOTERAPI PADA KASUS AUTISM SPECTRUM DISORDERS DI KLINIK BOYOLALI: CASE STUDY - Amini, Rozalina Anisyah; Tiara Fatmarizka; Intan Herlinawati (Journal of Innovation Research and Knowledge, 2022)
Introduction: Autism Spectrum Disorder (ASD) is considered a series of multifactorial neurodevelopmental disorders. It is characterized by impairments in social skills, communication and by the appearance of repetitive and stereotyped behaviors. Children with ASD usually perform repetitive actions such as clapping, moving, running back and forth, and so on. Objective: To determine the effectiveness of physiotherapy modalities in the form of eye contact exercise, brain gym, and blocking in ASD children. Method: Single-subject research conducted on 2-year-old children with ASD. Result: The evaluation was carried out using the Diagnostic and Statistical Manual of Mental Disorders (DSM-V). There is a decrease in severity from the initial measurement. Conclusion: There is a decrease in severity which shows a good direction after being given physiotherapy modalities for 4 weeks.